2014
DOI: 10.3109/03014460.2014.902991
|View full text |Cite
|
Sign up to set email alerts
|

Secular trends in Cherokee cranial morphology: Eastern vs Western bands

Abstract: These findings support negative secular trend occurring for both Cherokee bands where the environment made a detrimental impact; this is especially marked with the Western Cherokee band.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Kasai et al, [101] studied difference in Japanese and Australian aboriginal crania and found that the masticatory forces due to different food habits are responsible for the difference. Growth disturbances during early development also reflected in the craniofacial dimensions [8].…”
Section: Ambiguity In Nomenclature Of Indicesmentioning
confidence: 99%
See 3 more Smart Citations
“…Kasai et al, [101] studied difference in Japanese and Australian aboriginal crania and found that the masticatory forces due to different food habits are responsible for the difference. Growth disturbances during early development also reflected in the craniofacial dimensions [8].…”
Section: Ambiguity In Nomenclature Of Indicesmentioning
confidence: 99%
“…These craniometric indices may be affected by secular or temporal changes [8]. Secular changes are physical changes that may take place within the given population due to dramatic shifts in living standards or exposure to a new environment.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Data on these individuals were contributed to the FDB by a single practitioner over the same 2-month period and, though identified as Hispanic, their geographic origin is stated as unknown. This cluster also contains one White female from the Todd Collection, whose allocation is likely anomalous: her early birth year (1911) relative to the White female mean (1,946 6 22 years) may set her apart morphologically in light of arguments made for secular change in the cranium over the last century in U.S. populations (Jantz and Meadows Jantz, 2000;Wescott and Jantz, 2005;Sutphin et al, 2014).…”
Section: Discussionmentioning
confidence: 99%